Active maximum flexion after total knee arthroplasty is not related to posterior tibial slope, body mass index, or patient satisfaction: A retrospective cohort study. Issue 3 (27th May 2020) - Sciberras, Nadia C.; Deakin, Angela H.; Picard, Frederic
Abstract : Background: Postoperative active maximum flexion is a major contributor to effective knee function after total knee arthroplasty (TKA). The lack of posterior tibial slope and a high body mass index (BMI) have been identified among the causative factors of reduced maximum flexion. This study investigated the correlation between these factors and maximum flexion achieved. Methods: All patients included in this retrospective study had a primary navigated TKA using Columbus® CR-knee implants (Aesculap, Tuttligen, Germany) and the Orthopilot® (Aesculap, Tuttligen, Germany) navigation system. At the 6-week review patients underwent a CT. At 1 yr, active flexion was measured by independent arthroplasty practitioners, and patient satisfaction was recorded. All CT measurements were taken by an independent radiologist. Posterior slope was indicated by a positive value. Results: One hundred and eighty-six knees were included. The mean patient age was 68 yr and mean BMI was 31.0. The mean maximum active flexion at 1 yr was 103 degrees (SD 9 degrees, range, 83 to 130 degrees). The mean posterior tibial slope (bony cut) was 2 degrees (SD 2 degrees, range −2 to 5 degrees). There was no correlation between posterior tibial slope and maximum flexion, r=0.086 (95% CI −0.058 to 0.227, P =0.245) between flexion and BMI, r=−0.112 (95% CI −0.251 to 0.032, P =0.129). There was a weak correlation between posterior slope and extension achieved, r=0.198 (95% CI 0.056 to 0.332, P =0.007), but this had little clinical predictive value. There was no link between either maximum flexion or patient satisfaction. Conclusions: In this study, no relationship between posterior tibial slope or BMI and the degree of achieved active maximum flexion was found. Consequently, other factors should be considered when attempting to increase the maximum flexion achieved. Level of Evidence: Level III.